Improvement of Inceptisol Soil Chemistry and soybean growth Due to Composting Enriched Egg Shell And Zeolite - Irpan Ediar Pane; Tengku Sabrina; Alida Lubis (Universitas Sumatera Utara, 2018)
Availability of nutrients in the soil are the main factors that determine the growth and crop production. This research aims to know the response of compost enriched eggshells and zeolite on soil inceptisol of some aspects inceptisol soil properties and soybean growth. The research was conducted in UPT Palawija Tanjung Selamat land and Soil Biology Laboratory Faculty of Agriculture, University of North Sumatra. This research using a randomized block design factorial. The first factor is compost enriched eggshell consists of without compost, 10 tons / ha compost, 20 tons / ha compost, 30 tons / ha compost and The second factor is zeolite consists of without zeolite, 3 tons / ha zeolite, 3 tons / ha zeolite enriched green manure. The results showed that the compost enriched eggshell can increase soil pH, soil Ca exchange and soil organic in a linear, zeolite application can increase plant nitrogen absorption, interaction between compost enriched eggshell with zeolite can increase soil Ca exchange. Keywords: Availability of nutrients, Compost Enriched Eggshells, Inceptisol, Zeolite